2015
DOI: 10.16965/ijar.2015.154
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Evaluation of Foramen Magnum in Dry Human Skulls

Abstract: The foramen magnum is an important landmark in the posterior part of the cranial base, which is largely formed by the occipital bone. The dimensions of the foramen magnum are clinically important because of the vital structures passing through it. We studied thirty six dry human skulls of known sex and measured anteroposterior and transverse diameters with the help of Vernier caliper. Additionally, surface area and Index of foramen magnum were also calculated. Oval shape is the main type of morphological varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 38 publications
4
26
1
Order By: Relevance
“…Mean area in our study was found to be 714.99±0.844 mm 2 which is closer to study done by Singh [18] and Anil kumar 876 mm 2 [12].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Mean area in our study was found to be 714.99±0.844 mm 2 which is closer to study done by Singh [18] and Anil kumar 876 mm 2 [12].…”
Section: Discussionsupporting
confidence: 88%
“…The mean AP diameter in the present study was found to be less than that by Anil Kumar in 2015(36.78mm) [12] Jain D in 2014 (36.2mm) [13] and Burdan in 2012 (37.06mm) [14].…”
Section: Discussioncontrasting
confidence: 57%
“…Evaluation of these foramina is becoming an important part of diagnostic medicine and making difficult diagnosis of pathological conditions of skull foramina possible [13].…”
Section: Introductionmentioning
confidence: 99%
“…From an inferior view, there are ten skull base foramina conventionally described as constant: greater palatine, lesser palatine, lacerum, ovale, spinosum, external opening of the carotid canal, stylomastoid, jugular, mastoid, and external opening of the hypoglossal canal (Drake et al). These structures can be used to establish differences between different populations and ethnic groups, due to the fact that both their morphology and morphometry are particularly variable (Osunwoke et al, 2010;Khan et al, 2012;Osunwoke et al, 2012;Gupta et al, 2014;Kumar et al, 2015;Vidya et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al, 2011;Khan et al;Osunwoke et al, 2012;Gupta et al;Kumar et al;Raval et al, 2015;Vidya et al).…”
Section: Introductionmentioning
confidence: 99%